Expression of epithelial–mesenchymal transition driver brachyury and status of tumor-infiltrating CD8+ and FOXP3+ lymphocytes in predicting treatment responses to neoadjuvant chemotherapy of breast cancer - Kwan Ho Lee; Eun Young Kim; Yong Lai Park; Sung-Im Do; Seoung Wan Chae; Chan Heun Park (Tumor Biology)
Brachyury has been characterized as a driver of epithelial–mesenchymal transition process which is regarded as an important mechanism of cancer cell invasion and metastatic progression. The status of tumor-infiltrating lymphocytes has been proposed to predict response to neoadjuvant chemotherapy in breast cancer. We investigated the clinical significance and value of tumor-infiltrating lymphocytes and brachyury as biomarkers to predict treatment responses to neoadjuvant chemotherapy in breast cancer. We also examined the correlation of the Neo-Bioscore with tumor-infiltrating lymphocytes and brachyury to indirectly predict long-term outcome. This retrospective study included a series of 44 consecutive patients treated between January 2011 and December 2015. All patient samples were obtained using core needle biopsy before neoadjuvant chemotherapy. The relationship of expression of Brachyury and tumor-infiltrating lymphocyte subsets (CD8+, forkhead box protein 3 tumor-infiltrating lymphocytes) with clinicopathological factors was assessed to identify its predictive role with respect to tumor response to neoadjuvant chemotherapy and the outcome. Of 44 patients, 6 showed no response, 31 had partial response, and 7 demonstrated pathological complete response. Forkhead box protein 3 was significantly higher in the response group than in the no response group (no response = 2.6, partial response = 7.0, complete response = 9.7, p  = 0.020). Brachyury expression was inversely associated with response to neoadjuvant chemotherapy, but the difference was not statistically significant ( p  = 0.62). We also observed a significant association between forkhead box protein 3 ( p  = 0.001) and the Neo-Bioscore, while only a marginal difference was observed with CD8+ expression ( p  = 0.074). This study demonstrated that forkhead box protein 3 expression has value as the only independent marker that predicts a good response to neoadjuvant chemotherapy and that it is related with a good prognosis according to the Neo-Bioscore. Brachyury was significantly associated with estrogen receptor positive and human epidermal growth factor receptor 2 negative status; further study would be needed to clarify how it affects treatment prognosis.